To segment or not? That is the question. (January 2018) - Tkaczynski, Aaron; Rundle-Thiele, Sharyn R; Prebensen, Nina Katrine
While a plethora of studies exist identifying tourism segments, limited attention has been directed towards consideration of segment validation. Practically, such an assessment involves carefully thinking about appropriateness of segment selection. Failing to consider whether targeting segments is appropriate based on key criteria limits marketing potential as resources can be wasted targeting differences which are not meaningful. This article involves an assessment of segments using Kotler's (1988) four criteria to ascertain whether pursuit of different segments is warranted. A total of 2500 winter Northern Norway vacationers' data was analysed using TwoStep cluster analysis. Two segments were identified but close inspection of the segments using targeting criteria indicated the segments were not actionable. Managerial and research implications are outlined in addition to a research agenda to advance segmentation science.